Effects of CO2, Er:YAG, and Nd:YAG laser treatments on shear bond strength of resin cement to zirconia - Rahab Ghoveizi; Amirhosain Jafarbeigi; Maziar Mir; Abolghasem Mohammadi; Sara Tavakolizadeh (Journal of Dental Materials and Techniques)
AbstractObjective: This study aimed to evaluate the effect of different lasers at various settings on the shear bond strength (SBS) of resin cement to zirconia.Methods: In this in vitro study, 165 zirconia discs were divided into 11 groups (n=15). The groups underwent the following treatments: a control group with no treatment, a sandblasted group with 50 µm Al₂O₃, three groups treated with a CO₂ laser (4 W, 5 W, 6 W), three groups treated with an Er:YAG laser (3 W, 4 W, 6 W), and three groups treated with a Nd:YAG laser (2 W, 2.5 W, 3 W). Composite cylinders were bonded to the zirconia using resin cement. After 24 hours, the samples were thermocycled and SBS was measured using a universal testing machine. Data were analyzed by the Welch test and the Games-Howell test (α=0.05).Results: The sandblasted group exhibited the highest SBS, while the control group showed the lowest. A significant difference in SBS was observed between the groups (P<0.001). Pairwise comparisons revealed no significant differences between the sandblasted group and the Nd:YAG laser groups (2 W, 2.5 W, 3 W), the CO₂ laser group (6 W), and the Er:YAG laser group (6 W) (P > 0.05).Conclusions: Sandblasting with Al₂O₃ particles yielded the highest bond strength of resin cement to zirconia. Alternatively, Nd:YAG at all tested parameters, and Er:YAG, and CO₂ lasers at specific settings could be used to enhance bond strength to zirconia. Among lasers, the Nd:YAG laser at 2.5 W achieved the best performance.